Assessing the ecological-context strengths of school-based talent development programs in rugby league - Cupples, B.; O`Connor, D.; Cobley, S. (Research Quarterly for Exercise and Sport, 2021)
Purpose: Adopting an ecological perspective, the study explored the context-strengths of three successful school-based TDEs in rugby league.